Population-level association of layperson cardiopulmonary resuscitation training with survival after out-of-hospital cardiac arrest: a systematic review and meta-analysis - Pan Pan; Zhou YaXiong; Jiang YaoWen; Xia YiQin; Chen Yao (Frontiers in Public Health, 2026)
Background Out-of-hospital cardiac arrest (OHCA) is a significant worldwide cause of death and is highly dependent upon bystander intervention. Layperson cardiopulmonary resuscitation (CPR) training has been widely promoted, but its population-level association with survival after out-of-hospital cardiac arrest remains incompletely characterized. Methods This systematic review and meta-analysis was conducted according to PRISMA guidelines and registered in PROSPERO. PubMed, Embase, Web of science and Cochrane Library and major Chinese database were searched from inception to June 1, 2026. Studies evaluating the association between layperson CPR training and OHCA survival outcomes were included. The main outcome measure was survival to hospital discharge. Random-effects models were used for calculation of pooled odds ratios (ORs) and 95% confidence intervals (CIs). I 2 statistics and Egger’s / Begg’s tests were used to evaluate heterogeneity and publication bias. Results Nineteen observational studies comprising 159,378 participants from eight countries were included in the systematic review. Seventeen studies comprising 144,775 participants contributed to the training-modality-specific meta-analyses. Layperson CPR training was associated with higher survival to hospital discharge. In the training-modality-specific analyses, favorable associations were observed for both CPR-only training (OR = 1.74, 95% CI: 1.39–2.19) and CPR combined with AED training (OR = 1.42, 95% CI: 1.15–1.77). There was evidence of significant heterogeneity among the studies, but no evidence of publication bias. Conclusion Layperson CPR training was associated with higher population-level survival after OHCA and should be viewed as one component of an integrated community resuscitation system. Systematic review registration https://www.crd.york.ac.uk/prospero/record_view.phprecid=CRD420261479204 .